Representation of Ethical Issues and Social Reality in the Novel ‘Dua Garis Biru’ - Farah Nur Afifah; Anggi Yus Susilowati (Sociology Study Program, Faculty of Social Science and Law, Universitas Negeri Jakarta, 2026)
This study aims to analyse the representation of ethical issues and social realities ofadolescents in the film Dua Garis Biru (2019). Using qualitative research methods withcontent analysis techniques, this study examines how narrative and visual elements constructthe phenomenon of teenage pregnancy outside of marriage. The results show that this filmsuccessfully reflects moral dilemmas, social stigma, and systemic failures in sexualityeducation and family communication. The analysis reveals that this film functions as anagent of social discourse that challenges patriarchal culture and the myth of early marriageas the only solution. By promoting the ethics of shared responsibility, this film transformspersonal issues into collective concerns. The study concludes that Dua Garis Biru is notmerely entertainment, but a comprehensive sexual education tool that encourages society toshift from judgemental morality towards a more empathetic, inclusive, and responsiveapproach to adolescent rights.